2004
DOI: 10.1194/jlr.m300232-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Formation of 7-dehydrocholesterol-containing membrane rafts in vitro and in vivo, with relevance to the Smith-Lemli-Opitz syndrome

Abstract: Smith-Lemli-Opitz syndrome (SLOS) is a recessive disease typified by 7-dehydrocholesterol (7DHC) accumulation and depletion of cholesterol. Because cholesterol is a primary component of detergent-resistant membrane domains ("rafts"), we examined the compatibility of 7DHC with raft formation. Liposomes containing bovine brain phosphatidylcholine, sphingomyelin, cerebrosides, and either cholesterol, 7DHC, or coprostanol (the latter being incompatible with raft formation) were prepared. 7DHC was indistinguishable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(97 citation statements)
references
References 49 publications
3
93
0
1
Order By: Relevance
“…Nevertheless, 7DHC is the prominent sterol in the SLOS membrane and the biophysical parameters of Kv1.3 gating were similarly affected in SLOS and in T cells treated with MβCD/7DHC complex. This suggests that acute loading of T cells with 7DHC mimics adequately the effect of the lipid milieu existing in SLOS on the operation of Kv1.3 [11,29,30,54,68].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Nevertheless, 7DHC is the prominent sterol in the SLOS membrane and the biophysical parameters of Kv1.3 gating were similarly affected in SLOS and in T cells treated with MβCD/7DHC complex. This suggests that acute loading of T cells with 7DHC mimics adequately the effect of the lipid milieu existing in SLOS on the operation of Kv1.3 [11,29,30,54,68].…”
Section: Discussionmentioning
confidence: 84%
“…The effect of 7DHC on the biophysical properties of the cell membrane is contradictory. For example, it has been demonstrated that 7DHC destabilizes cholesterol rich domains, increases the membrane fluidity and alters the protein pattern of rafts [11,30,61]. On the contrary, according to Liu et al, the difference between CHOL and 7DHC from the perspective of membrane ordering and condensation is essentially imperceptible [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility that protein-protein or protein-lipid interactions stabilize small transient domains and/or induce the formation of larger, longer-lived entities has been proposed by a number of groups (Kusumi et al 2004;Kusumi and Suzuki 2005;Hancock 2006;Jacobson et al 2007). Finally, the possibility that cell membranes exist close to a phase boundary and thus small changes in lipid composition could drive raft assembly or disassembly has also been suggested (Keller et al 2004;Veatch and Keller 2005). …”
Section: Molecular Mechanisms Underlying Raft Formation and Functionmentioning
confidence: 99%
“…This elevation in 7-dehydrocholesterol inhibits the activity of Hmgcr, thus further exacerbating the cholesterol deficit (Honda et al 1998;Fitzky et al 2001). Importantly, as 7-dehydrocholesterol can incorporate into lipid rafts and alters the protein composition within it (Keller et al 2004), at least some of the disturbances seen in SLOS can be due to the altered function of the lipid rafts. The greatly increased level of 7-dehydrocholesterol leads to increased membrane fluidity and decreased intermolecular packing of phospholipids fatty acyl chains (Vainio et al 2006;Rog et al 2007;Samuli Ollila et al 2007).…”
Section: Human Conditions With Altered Cholesterol Biosynthesis: Consmentioning
confidence: 99%